Investigating trophic interactions between parasites and their marine fish hosts using stable isotope analysis - Weston, Mark Jonathan (Department of Biological Sciences, 2018)
Parasitism is accepted as being an essential driver in the organization of biological communities. However, although there are estimated to be more parasitic than free-living organisms, parasites have been largely neglected from ecological studies and we have a relatively limited understanding of their trophic ecology. Hence, in order to incorporate parasites into food-web models and ecological studies, basic trophic interactions between parasites and their hosts need to be assessed. Here, I investigated host-parasite interactions using stable isotope analyses on a broad range of marine fish hosts and their associated copepod and monogenean gill parasites. The study also provides insight into the gill parasite diversity of a number of host species from South African marine waters. Seventeen species of fish hosts, ranging from lower to upper trophic levels, were collected from South African waters in 2015 and 2016 during surveys conducted by the Department of Agriculture, Forestry and Fisheries from South African waters. These host species were; Thunnus albacares, Thunnus maccoyii, Thunnus alalunga, Thunnus obesus, Isurus oxyrinchus, Prionace glauca, Xiphius gladius, Brama brama, Thyrsites atun, Seriola lalandi, Sarda sarda, Genypterus capensis, Merluccius paradoxus, Merluccius capensis, Lampanyctodes hectoris, Sardinops sagax and Trachurus capensis. The head region, gills and operculae from a total of 1513 fish were examined and any ectoparasites removed, identified down to the lowest taxonomic level possible, and counted. A total of 32 parasite taxa, comprising 20 copepods and 12 monogenean species, were recorded. Two new host records and 15 new geographic records for South Africa were catalogued. The new host records are Mazocraes sp. infecting T. atun, and Caligus dakari infecting T. capensis. The new locality records consist of Euryphorus brachypterus recovered from T. alalunga and T. obesus, Pseudocycnus appendiculatus recovered from T. albacares, T. alalunga and T. obesus, Hexostoma sp. recovered from T. albacares and T. obesus, Nasicola klawei recovered from T. albacares and T. obesus, Tristoma adcoccineum recovered from X. gladius, Eobrachiella elegans and two species from the genus Parabrachiella recovered from S. lalandi and Anthocotyle merlucci recovered from M. paradoxus and M. capensis. These new records have substantially contributed to the known parasite biodiversity within the South African marine environment. Host-parasite interactions between 15 species of fish host and their copepod and monogenean gill parasites were investigated by means of stable isotope analysis. Host white muscle tissue, host gill tissue and parasite samples were analysed for their carbon and nitrogen isotopic signatures. Results indicated that δ¹⁵N is tissue-specific, with host white muscle tissue showing significantly greater enrichment in ¹⁵N compared to host gill tissue (n =60; Z=5.66843; p<0.00001), and as gill tissue is what the parasites are presumably feeding on, host gill tissue was therefore selected as the most appropriate proxy.